Entendendo as propriedades do arenito Botucatu e sua utilização como meio poroso para estudos envolvendo o deslocamento de fluidos poliméricos - Cardoso, Oldemar Ribeiro (2014)
The development of products whose purpose is to promote blockages in high permeability zones as well as to control the hydrate or scale formation also needs some tests in porous media before using the product in the field, where attempts and unavoidable operational errors costs would able to derail any projects. The aim of this study was to analyze and compare the Botucatu and Berea sandstones properties, involving problems related to loss permeability. It was observed that even cores of Berea, without expansible clays in their composition had their permeability reduced, as soon as the salinity of brine reached a lower limit. As expected, the same happened with the Botucatu sandstone samples, however, in this case, the sensitivity to low salinity was more pronounced. In a second phase, the research was focused on the Botucatu Sandstone behavior front of dilute polymer solutions injection, checking the main relationships between the Rock / Fluid interactions, considering the Mobility Reduction, Resistance and Residual Resistance Factors, as well as adsorption/desorption processes of these polymers, and the polymer molecules average size and porous sandstone average size ratio. The results for both phases showed a real feasibility of using the Botucatu sandstone in laboratory tests whose objective is the displacement of fluids through porous media